A novel feedback regulated loop of circRRM2-IGF2BP1-MYC promotes breast cancer metastasis - Ran Hao; Lei Zhang; Yangming Si; Peng Zhang; Yipeng Wang; Bangchao Li; Jie Hu; Yixin Qi (Cancer Cell International, 2023)
Abstract Background Metastasis is the leading cause of mortality in patients with breast cancer (BC). Studies demonstrate that circular RNAs (circRNAs) were involved in BC progression, while the molecular mechanisms remain largely unclear. Methods The microArray circRNA profiles were used to explore the differential expression circRNAs in BC and paracancerous normal tissues, and the quantitative reverse transcription-polymerase chain reaction was used to validate their expression level in clinical samples and cell lines. Nuclear/cytosolic fractionation and fluorescence in situ hybridization (FISH) assays were performed to examine circRRM2 (hsa_circ_0052582) subcellular location. The scratch wound healing and transwell assays were conducted to evaluate the impact of circRRM2 on BC cell migration and invasion. We predicted miRNAs that might bind with cricRRM2 and the downstream target genes using bioinformatics analysis and explored their expression levels and prognostic value in BC. FISH, RNA immunoprecipitation, Co-immunoprecipitation, Western blot, and rescue experiments were implemented to figure out circRRM2 function and underlying mechanisms in BC. Results The present study revealed several aberrant circRNAs in BC tissues and observed that circRRM2 was upregulated in tumor tissues of 40 patients with BC. High circRRM2 was significantly associated with advanced N stage in patients with BC. Gain- and loss- of function experiments revealed that circRRM2 promoted the migration and invasion of cells and functioned as an oncogene in BC. Mechanism studies showed that circRRM2 competed with miR-31-5p/miR-27b-3p to upregulate the IGF2BP1 expression. Furthermore, IGF2BP1 upregulated the circRRM2 level via interacting with MYC, which functioned as the transcriptional factor of circRRM2. Thus, the positive feedback loop that was composed of circRRM2/IGF2BP1/MYC was identified. Conclusion This study confirms that upregulated circRRM2 functions an oncogenic role in BC metastasis. The positive feedback loop of circRRM2/IGF2BP1/MYC enforces the circRRM2 expression, which might offer a potential target for BC treatment.